2015
DOI: 10.1007/s11626-015-9866-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human skin-derived precursor cells into functional islet-like insulin-producing cell clusters

Abstract: Advances in cell-replacement strategies for diabetes have focused on renewable sources of glucose-responsive, insulin-producing cells (IPCs). One of the most proper alternatives is multipotent skin-derived precursors cells (SKPs), which can be differentiated into IPCs. In this study, we reported the isolation and expansion of human skin-derived precursors (hSKPs) followed by their differentiation into IPCs in vitro, through exposure to suitable differentiation factors. The gene expression of endocrine β cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Human skin-derived precursors are a promising postnatal stem cell population for cellular therapy, as they exhibit multilineage differentiation capacity [5,7,8,16,19,22]. Furthermore, we previously showed that SKP are poorly immunogenic and exhibit favorable immunosuppressive properties [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human skin-derived precursors are a promising postnatal stem cell population for cellular therapy, as they exhibit multilineage differentiation capacity [5,7,8,16,19,22]. Furthermore, we previously showed that SKP are poorly immunogenic and exhibit favorable immunosuppressive properties [23].…”
Section: Discussionmentioning
confidence: 99%
“…SKP are of particular interest for regenerative medicine as they share several properties with embryonic neural crest-derived stem cells, a group of highly plastic cells with unique properties that reside within the developing embryo [2,12,13]. In particular, we and others have shown that SKP are able to generate (1) neuronal cells such as Schwann cells [7,14,15], catecholaminergic [16], dopaminergic [17] and enteric [18] neurons, (2) mesodermal cell types including adipocytes, chondrocytes, osteocytes [2] and vascular smooth muscle cells [19] and (3) endodermal progeny such as hepatic cells [5,9,20,21] and islet-like insulin-producing cells [22].…”
Section: Introductionmentioning
confidence: 98%
“…Beta cells have been obtained from embryonic stems cells (ESC) of both mouse [8] and human origin [9] (reviewed in [10]), or from induced pluripotent stem cells (iPSC) produced through direct transcriptional reprogramming using stemness transcription factor cocktails (reviewed in [1013]), or through reprogramming via a lineage conversion strategy from fibroblasts [14]. Although still controversial [15], a number of studies have described techniques for inducing the beta cell-specific reprogramming of fibroblasts of multiple origins into glucose-responsive beta-like cells [1618]. However, long-term approaches involving differentiation of iPSC and ESC are compromised by the latent potential of residual tumor-promoting stem cells to develop into teratomas or cause tumorigenesis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Skin-derived precursors were converted in vitro into cells capable of glucose-dependent insulin and С-peptide secretion. The obtained cells expressed markers such as Pdx1, Nkx2.2, Pax4, NeuroD, and Isl1 found in mature β-cells [149].…”
Section: Application Of Committed Celsmentioning
confidence: 92%